2021
DOI: 10.1002/rcm.9066
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric study of ceramics in the Sm2O3‐ZrO2‐HfO2 system at high temperatures

Abstract: Rationale Systems containing zirconia, hafnia, and rare earth oxides are indispensable in various areas of high‐temperature technologies as a basis of ultra‐high refractory ceramics. Exposure of these materials to high temperatures may result in unexpected selective vaporization of components or phase transitions in the condensed phase leading to changes in physicochemical properties. Consequently, reliable application of the ceramics based on systems such as Sm2O3‐ZrO2‐HfO2 is impossible without data on its v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…KEMS studies on the following relevant systems have recently been reported: Sm 2 O 3 ‐ZrO 2, 67,305 UO 2 ‐ZrO 2, 306 and Sm 2 O 3 ‐ZrO 2 ‐HfO 2. 244,307 …”
Section: Novel Applications Of Kemsmentioning
confidence: 99%
“…KEMS studies on the following relevant systems have recently been reported: Sm 2 O 3 ‐ZrO 2, 67,305 UO 2 ‐ZrO 2, 306 and Sm 2 O 3 ‐ZrO 2 ‐HfO 2. 244,307 …”
Section: Novel Applications Of Kemsmentioning
confidence: 99%